2013
DOI: 10.1111/tmi.12112
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles culicifacies sibling species in Odisha, eastern India: First appearance of Anopheles culicifacies E and its vectorial role in malaria transmission

Abstract: Abstractobjective To identify the Anopheles culicifacies sibling species complex and study their vectorial role in malaria endemic regions of Odisha.methods Mosquitoes were collected from 6 malaria endemic districts using standard entomological collection methods. An. culicifacies sibling species were identified by multiplex polymerase chain reaction (PCR) using cytochrome oxidase subunit II (COII) region of mitochondrial DNA. Plasmodium falciparum (Pf) sporozoite rate and human blood fed percentage (HBF) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…culicifacies and An . fluviatilis in feeding preference, resting behavior and infection rates in different states [ 11 ], [ 12 ], [ 13 ], [ 14 ]. These differences are likely to be due to the fact that these are a complex of sibling species with differing behaviours and vector capacities.…”
Section: Introductionmentioning
confidence: 99%
“…culicifacies and An . fluviatilis in feeding preference, resting behavior and infection rates in different states [ 11 ], [ 12 ], [ 13 ], [ 14 ]. These differences are likely to be due to the fact that these are a complex of sibling species with differing behaviours and vector capacities.…”
Section: Introductionmentioning
confidence: 99%
“…Species D is sympatric with species A and B in northwestern region, and with species A, B and C in central India and a few areas in southern India. Species E is sympatric with species B in southern Tamil Nadu including Rameshwaram islands and Sri Lanka, and there are reports of expansion of distribution range of species A, D and E in Odisha and that of species E in Madhya Pradesh but these investigations lack the component of chromosome analyses for diagnostic confirmation 53 54 55 . The proportions of sibling species, however, varied in different geographical zones and seasons, e.g.…”
Section: Sibling Species Distribution and Sympatricitymentioning
confidence: 99%
“…3 ). Taking cognizance of the biological differences of sibling species, the rural India is stratified into seven divisions (excluding urban metropolitan cities) for benefit of prioritizing vector control options ( Table III ) 53 54 55 56 57 .…”
Section: Vector Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In Odisha, recent findings revealed invasion by An. culicifacies sibling species ‘A’, ‘D’ and ‘E’ (the latter species being the most efficient vector of the complex), in addition to prevalent species ‘B’ and ‘C’ amounting to added transmission [73, 74]. It was observed that given the population diminution in human dwellings (indoors), An.…”
Section: Introductionmentioning
confidence: 99%